STUDY OF APPLICATION OF KOREAN ALPHABET AMONG CIA-CIA TRIBE IN BAUBAU CITY - Paramita, Winda; ", Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research explain about the study of application of Korean Alphabet among Cia-Cia tribe in Baubau city. The aims of applying the Korean alphabet (hangeul) in the town of Baubau is to preserve the language of the Cia-Cia tribe areas as they did not have a writing system. Therefore, the city Government South Korea and the Government of Baubau, alongside with Hunminjeongeun Research Institude cooperate to the Cia-Cia region through research.This research uses construtivism and national interest. It also uses level analysis is Nation-State. This research uses qualitative method and library research. And applying the questions to the parties who are involed in this research through media.The implementation of Korean alphabet (hangeul) in the town of Baubau gives impact on developments in various fields, especially in the field of education society which support the society of Cia-Cia and the area around the town of Baubau.Keywords: Cia-Cia, Baubau, Hangeul, South Korea